FLNC-Associated Myofibrillar Myopathy: New Clinical, Functional, and Proteomic Data. (June 2021) - Kley, Rudolf Andre; Leber, Yvonne; Schrank, Bertold; Zhuge, Heidi; Orfanos, Zacharias; Kostan, Julius; Onipe, Adekunle; Sellung, Dominik; Güttsches, Anne Katrin; Eggers, Britta; Jacobsen, Frank; Kress, Wolfram; et al.
Abstract : Objective: To determine whether a new indel mutation in the dimerization domain of filamin C (FLNc) causes a hereditary myopathy with protein aggregation in muscle fibers, we clinically and molecularly studied a German family with autosomal dominant myofibrillar myopathy (MFM). Methods: We performed mutational analysis in 3 generations, muscle histopathology, and proteomic studies of IM protein aggregates. Functional consequences of the FLNC mutation were investigated with interaction and transfection studies and biophysics molecular analysis. Results: Eight patients revealed clinical features of slowly progressive proximal weakness associated with a heterozygous c.8025_8030delCAAGACinsA (p.K2676Pfs*3) mutation in FLNC . Two patients exhibited a mild cardiomyopathy. MRI of skeletal muscle revealed lipomatous changes typical for MFM with FLNC mutations. Muscle biopsies showed characteristic MFM findings with protein aggregation and lesion formation. The proteomic profile of aggregates was specific for MFM-filaminopathy and indicated activation of the ubiquitin-proteasome system (UPS) and autophagic pathways. Functional studies revealed that mutant FLNc is misfolded, unstable, and incapable of forming homodimers and heterodimers with wild-type FLNc. Conclusions: This new MFM-filaminopathy family confirms that expression of mutant FLNC leads to an adult-onset muscle phenotype with intracellular protein accumulation. Mutant FLNc protein is biochemically compromised and leads to dysregulation of protein quality control mechanisms. Proteomic analysis of MFM protein aggregates is a potent method to identify disease-relevant proteins, differentiate MFM subtypes, evaluate the relevance of gene variants, and identify novel MFM candidate genes.